Bilateral Sustainable Development Dialogue: Sustainable Development Indicator System in the UK and Green GDP in China - Guo, Yingli (2007)
In 2005, the United Kingdom (UK) embarked on a pro-active new partnership known as Sustainable Development Dialogues (SDDs) with rapidly developing countries. This study focuses on the bilateral UK-China SDD and aims to address whether the measurement practices - the UK Sustainable Development Indicator (SDI) System and Green Gross Domestic Product (GDP) in China can be shared in order to help mainstream Sustainable Development (SD) more effectively in both countries. First, the literature on measuring SD is reviewed; which not only provides the basis of in-depth interviews, but also forms the line of inquiry to address the research question. Based on the interviews and relevant literature, the main findings are reported by presenting how the UK has been developing SDIs and how China has been exploring Green GDP. Then, according to the purpose of the study, a strength and weakness evaluation, as well as a Political, Economic, Social and Technological (PEST) factors analysis are used to analyze the findings. Both the findings and analysis of the findings are related back to the theory identified in the literature review. This study concludes that the UK SDI System and the Green GDP in China have constraints and benefits respectively. The different institutional contexts in the UK and China may be the main reason for the two countries to select and implement the current measurement practices. Although there is no consensus on whether the measurement practices in one country can be shared by the other country, the majority of interviewees support the idea that the two countries could usefully share measurement practices. Since neither side is fully aware of the present measurement practices in the other country, further communication between the two countries about the measurement practices and external environments is recommended.